Effectiveness, Consumer’s Perception, and Behavior Towards Healthier Choice Logo on Indonesian Instant Noodles in Jakarta - Kumarga, Melania Febriana; Muhandri, Tjahja; Hasanah, Uswatun (Jurnal Gizi dan Pangan, 2024)
This study was conducted to identify the availability of instant noodle products with and without the Healthier Choice (HC) logo that reflects Indonesian instant noodles nutrition labelling uptake by the food industry as well as to investigate the logo’s effectiveness in influencing customers to choose healthier noodle products and consumers’ perception and behavior toward the HC logo. Quantitative research consists of a market survey on HC logo usage in 120 instant noodle variants with different brands and an online consumer survey with a voluntary sampling technique involving 458 consumers aged 18‒68 years residing in Jakarta. Nutritional information data (total fat, saturated fat, sodium and sugar) in two groups of products (HC and without HC (WHC) groups) was analyzed using t-test, while the consumer survey data was analyzed using t-test and ANOVA. The confidence level used in statistical analysis was 95%. Of only eleven products that featured the HC logo on the packaging, one did not fulfill the criteria. The t-test showed no significant differences between products “without HC logo” and “with HC logo” groups in all nutrition content except for sodium. The HC logo showed significant difference in effectiveness for different gender and age groups, it was better for women than man, and older (43−58 and 59−68) more effective than younger (16−26 and 27−42). The consumer perception and behavior was more affected the age group 43−58 and 59−68 than 16−26 and 27−42, the level of education group in elementary, junior, and senior high school also post graduate group more influenced than pre-university and bachelor, consumption pattern moderate and frequent better than seldom consumption. Further, the consumer behavior also more influenced all income level group except >IDR20 million group.